Once bitten twice shy: longterm behavioural changes caused by trapping experience in willow warblers Phylloscopus trochilus - Linhart, Pavel (Jihočeská univerzita, 2014)
In this study, we provide an evidence that willow warblers captured into mist nets by using conspecific male playback avoided the playback and the mist net on future capture attempt. Whether the subsequent capture attempt was carried out within a same breeding season or in a following breeding season, the results were very similar suggesting that the situation is very strongly memorized by willow warblers. Such a behavioural changes leading to "trap shyness" could potentially affect population dynamics estimates and behavioural data based on playback captures or playback provocation in willow warblers but very likely in many other species as well.
Once bitten twice shy: longterm behavioural changes caused by trapping experience in willow warblers Phylloscopus trochilus
Keywords: mist-netting; aversive learning; playback capture; songbird; long-term memory; mist-netting; aversive learning; playback capture; songbird; long-term memory